Banks' trading after the Lehman crisis: The role of unconventional monetary policy - Natalia Podlich; Isabel Schnabel; Johannes Tischer (Deutsche Bundesbank, 2017)
Based on a detailed trade-level dataset, we analyze the proprietary trading behavior of German banks in the months directly preceding and following the Lehman collapse in September 2008. The default of Lehman Brothers was a shock to the German banking system that was both unexpected and exogenous. We examine banks' immediate reactions as well as their responses to unconventional monetary policy measures introduced shortly after the event - the introduction of full allotment and the change in eligibility criteria for collateral in central bank refinancing operations. Our results show that market liquidity tightened after the Lehman collapse but there is no evidence of fire sales in the German banking sector. Instead, we observe a broad-based flight to liquidity. The European Central Bank's unconventional monetary policy had a strong impact on banks' trading behavior by inducing shifts towards eligible securities and reducing pressure on market liquidity. This suggests that the ECB's measures contributed to stabilizing the financial system after the Lehman collapse.
Keywords: E44; E50; G01; G11; G21; 330; proprietary trading; fire sales; flight to liquidity; Lehman crisis; market liquidity; unconventional monetary policy